Firm-Level Determinants of Sustainability Practices in the UK Banking Sector: A Stakeholder Perspective - Echem, Kaodilichukwu Augustine; Ekemezie, Ekene (Prodi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Bunga Bangsa Cirebon, 2025)
The primary objective of this study was to understand the key factors that influence the adoption of sustainability practices within banks, focusing on firm-level factors. The research employed an online survey targeting stakeholders in the UK banking sector, using structured questions to assess perceptions of sustainability practices and their alignment with financial goals. The findings revealed that, while UK banks are increasingly adopting sustainable lending and investment practices, there remains a stronger emphasis on financial performance over sustainability goals. Banks often prioritize their reputation and brand image, with customer demand playing a significant role in shaping sustainability practices. Furthermore, the study found that banks in the UK provide sufficient sustainability-related disclosures to stakeholders, meeting growing expectations for transparency. In conclusion, the study emphasizes the need for UK banks to integrate sustainability into their core strategies, balancing financial performance with environmental and social goals. The research recommends that banks strengthen their commitment to sustainability by aligning their operations more closely with stakeholder expectations and enhancing sustainability reporting practices. Additionally, policymakers should consider incentivizing sustainability practices to further promote environmental responsibility within the banking sector.